The Determinants of Innovative Knowledge Transfer on Driving force Innovation Performance and Global innovation in MNC’s Automobile in Thailand - Boonsuwan, Phairat; Siriwichai, Chalermporn (Rajapark Journal, 2023)
The paper proposes a model explaining the innovations in organization on supporting local innovation, internal/external integration capacity and strategic alliances/partnership from international business literature thru innovative knowledge transfer by knowledge replication and knowledge adaption on innovation in organization as automobile MNCs in Thailand. Thus, a process reviewing the literature become an integral part of organizations’ business strategies, along with aiding organizations to grow and innovate in the global market and gain competitive advantage. The role of innovative knowledge transfer in fostering knowledge quality and how integrated innovation capability of an organization. Specifically, to explain the potential of innovative knowledge transfer dimension as knowledge replication and knowledge adaptation becoming to the efficiency of innovation performance and global innovation by compose a set of constructs through structured questionnaire on 380 respondents from the automobile industrial domain in Thailand. The results verify that relationship strength by 12 hypotheses were derived based on the identified constructs and were subsequently validated has a significant positive impact on the validating the hypotheses, it was observed that while organizational contexts were positive associated with innovative knowledge transfer. Additionally, it was also observed that both innovative knowledge transfer and the quality of knowledge were positively to innovation performance and global innovation.